Differential susceptibility of SARS‐CoV‐2 in animals: Evidence of ACE2 host receptor distribution in companion animals, livestock and wildlife by immunohistochemical characterisation. Issue 4 (26th July 2021) - Lean, Fabian Z. X.; Núñez, Alejandro; Spiro, Simon; Priestnall, Simon L.; Vreman, Sandra; Bailey, Dalan; James, Joe; Wrigglesworth, Ethan; Suarez‐Bonnet, Alejandro; Conceicao, Carina; Thakur, Nazia; Byrne, Alexander M.P.; et al.
Abstract: Angiotensin converting enzyme 2 (ACE2) is a host cell membrane protein (receptor) that mediates the binding of coronavirus, most notably SARS coronaviruses in the respiratory and gastrointestinal tracts. Although SARS‐CoV‐2 infection is mainly confined to humans, there have been numerous incidents of spillback (reverse zoonoses) to domestic and captive animals. An absence of information on the spatial distribution of ACE2 in animal tissues limits our understanding of host species susceptibility. Here, we describe the distribution of ACE2 using immunohistochemistry (IHC) on histological sections derived from carnivores, ungulates, primates and chiroptera. Comparison of mink ( Neovison vison ) and ferret ( Mustela putorius furo ) respiratory tracts showed substantial differences, demonstrating that ACE2 is present in the lower respiratory tract of mink but not ferrets. The presence of ACE2 in the respiratory tract in some species was much more restricted as indicated by limited immunolabelling in the nasal turbinate, trachea and lungs of cats ( Felis catus ) and only the nasal turbinate in the golden Syrian hamster ( Mesocricetus auratus ). In the lungs of other species, ACE2 could be detected on the bronchiolar epithelium of the sheep ( Ovis aries ), cattle ( Bos taurus ), European badger ( Meles meles ), cheetah ( Acinonyx jubatus ), tiger and lion ( Panthera spp .). In addition, ACE2 was present in the nasal mucosa epithelium of the serotine bat ( Eptesicus serotinus ) but not in pig ( Sus scrofa domestica ), cattle or sheep. In the intestine, ACE2 immunolabelling was seen on the microvillus of enterocytes (surface of intestine) across various taxa. These results provide anatomical evidence of ACE2 expression in a number of species which will enable further understanding of host susceptibility and tissue tropism of ACE2 receptor‐mediated viral infection.